Smart System Electricity Power Companies - K Naresh,; Sadla Naveen, (International Journal of Scientific Research in Science and Technology, 2025)
The integration of smart systems in electricity power companies is revolutionizing power distribution by enhancing efficiency, reliability, and sustainability. Powered by Artificial Intelligence (AI) and data analytics, these systems allow real-time monitoring, control, and optimization of the electricity grid. Smart grids, at the heart of this transformation, utilize sensors, communication networks, and automation to enable predictive maintenance, load balancing, and fault detection, reducing downtime. Smart meters offer consumers detailed insights into energy use, promoting informed consumption and supporting demand-side management. Benefits include lower operational costs, improved grid resilience, and better integration of renewable energy sources like solar and wind. Consumers enjoy transparent billing and potential savings via off-peak energy use programs. However, challenges such as high implementation costs, cybersecurity concerns, and infrastructure integration must be addressed. Effective collaboration among governments, utilities, and tech developers, along with robust regulations, is crucial. Ultimately, smart systems are key to achieving a more resilient, efficient, and sustainable global energy landscape.
Keywords: Smart Systems; Electricity Power Companies; Smart Grids; Artificial Intelligence (AI); Data Analytics; Renewable Energy; Demand-Side Management; Grid Resilience